Impaired lung function and associated risk factors in children born prematurely: a systematic review and meta-analysis - Menne R. van Boven; Gerard J. Hutten; Rianne Richardson; Marsh Königs; Aleid G. Leemhuis; Wes Onland; Suzanne W.J. Terheggen-Lagro; Jaap Oosterlaan; Anton H. van Kaam (European Respiratory Review)
Background Immature lung development and respiratory morbidity place preterm-born children at high risk of long-term pulmonary sequelae. This systematic review and meta-analysis aims to quantify lung function in preterm-born children and identify risk factors for a compromised lung function. Methods We searched MEDLINE, Embase, Cochrane Library, Web of Science and Scopus for relevant studies published on preterm cohorts born since 1990. Studies comparing forced expiratory volume in 1 s (FEV1) in preterm-born children aged ≥5 years to term-born controls or normative data were included. Study quality was assessed using the Newcastle–Ottawa Scale for cohort studies. Standardised mean differences in FEV1 and secondary spirometry outcomes per study were pooled using meta-analysis. The impact of different demographic and neonatal variables on studies’ FEV1 effect sizes was investigated by meta-regression analyses. Certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluations framework. Results We identified 42 studies with unique cohorts including 4743 preterm children and 9843 controls. Median gestational age in the studies was 28.0 weeks and age at assessment ranged from 6.7 to 16.7 years. Preterm children had lower FEV1 than controls (−0.58 sd, 95% CI −0.69– −0.47 sd, p<0.001) resulting in a relative risk of 2.9 (95% CI 2.4–3.4) for abnormal outcome, with high certainty of evidence. FEV1 was significantly associated with gestational age, birthweight, bronchopulmonary dysplasia and invasive mechanical ventilation in univariate meta-regression analyses (R2=36–96%). Conclusion This systematic review shows robust evidence of impaired lung function in preterm-born children with a high certainty of evidence.